Risk Factors for Postoperative Major Morbidity, Anastomotic Leakage, Re-Surgery and Mortality in Patients with Colonic Perforation. - Brunner, Maximilian; Gärtner, Lara; Weiß, Andreas; Weber, Klaus; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert (Journal of Clinical Medicine, 2024)
Background/Objectives: This study aimed to determine the risk factors associated with postoperative major morbidity, anastomotic/suture leakage, re-surgery and mortality in patients undergoing emergency surgery for colonic perforation. Methods: A total of 204 adult patients treated surgically for colonic perforation from 2016 to 2021 at the University Hospital Erlangen were included in a retrospective analysis. Patient demographics and pre-, intra- and postoperative parameters were obtained and evaluated among various outcome groups (in-hospital major morbidity, anastomotic/suture leakage, re-surgery and 90-day mortality). Results: Postoperative in-hospital major morbidity, anastomotic/suture leakage, need of re-surgery and 90-day mortality occurred in 45%, 12%, 25% and 12% of the included patients, respectively. Independent risk factors for in-hospital major morbidity were identified and included the presence of any comorbidity, a significantly reduced preoperative general condition, the localization of perforation in the right hemicolon and the need for an intraoperative blood transfusion. The only independent risk factor for anastomotic/suture leakage was the presence of any comorbidity, whereas no independent risk factors for re-surgery were found. An age > 65 years, a significantly reduced preoperative general condition and the need for an intraoperative blood transfusion were independent risk factors for 90-day mortality. Conclusions: Our study identified risk factors impacting postoperative outcomes in patients undergoing emergency surgery for colonic perforation. These patients should receive enhanced postoperative care and may benefit from individualized and targeted therapeutic approaches.
EVALuna2:582568